An updated checklist of bony fishes from the Persian Gulf - Taghavimotlagh, Seyed Aminollah; Kaymaram, Farhad; Vahabnezhad, Arezoo; Daryanabard, Gholamreza (Zootaxa, 2024)
This study provides an updated and comprehensive checklist of bony fishes occurring in the Persian Gulf based on a recent survey of the region. This study was conducted from 1995 to 2020 by research trawl survey for identification and biomass estimation of the demersal species each year from autumn to late winter, covering all waters of Iran in the Persian Gulf. In addition to the research cruises, routine field visits were conducted at major fishing ports to identify pelagic species captured through gillnet and trap fisheries. Among the over 700 species reported in previous studies conducted in the Persian Gulf, the occurrence of 486 species has been confirmed. Several species were omitted from the revised checklist due to insufficient evidence supporting their occurrence in the region or due to taxonomic confusion. Throughout the study, 486 species of bony fishes, representing 101 families, were identified, and a critical review of relevant literature was conducted. This checklist serves as a reliable reference to address existing contradictions in the scientific literature on bony fishes of the Persian Gulf and establishes a foundation for future stock assessment studies in the region.